IR Communication-Based Alternative Horn Signaling System for Vehicles to Reduce Sound Pollution (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract— Noise pollution has become a significant environmental issue, with the frequent use of vehicle horns being a major factor. This study presents a creative approach titled “IR Communication-Based Alternative Horn Signaling System for Vehicles to Reduce Sound Pollution,” which aims to reduce horn usage in road traffic, particularly on highways, by implementing infrared (IR) communication technology. The objective of this project is to identify effective alternatives that allow vehicles to communicate without relying on horn usage, thereby decreasing overall sound pollution. Specifically, the proposed system is intended to enhance communication between vehicles on highways and where traditional horn signaling is inappropriate, such as near schools and hospitals. In urban areas, drivers typically use horns within 10 to 30 meters, with a range of 30 to 50 meters in other situations. This system achieves 100% accuracy within 20 meters and at least 92% accuracy up to 50 meters. The system uses two ATtiny85 microcontrollers: Microcontroller-1 for transmission and Microcontroller-2 for reception. Microcontroller-1 connects to a push button and three IR LEDs, while Microcontroller-2 connects to an IR receiver (TSOP-1838 sensor) and a combination of LED and buzzer. By allowing vehicles to communicate without audible horns, this project seeks to reduce noise pollution, especially in low-traffic areas significantly. The findings indicate that this IR communication system could effectively enhance vehicle communication while also contributing to lower noise pollution levels.